1994
DOI: 10.1007/s004310050176
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability in the Baller-Gerold syndrome: report of a mildly affected patient and review of the literature

Abstract: We report a patient with a mild form of the Baller-Gerold syndrome (craniosynostosis-radial aplasia syndrome). The patient, a 3-year 3 month-old boy, has trigonocephaly with bilateral absent radii and thumbs. His growth parameters and psychomotor development have been normal. No visceral anomalies were found. This patient represents a new case of the rare mild form of the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The wide phenotypic variability of what is considered Baller-Gerold syndrome in combination with the numerous reports of overlap with other disorders and revised diagnoses has led several investigators to question whether Baller-Gerold syndrome is a distinct entity [Cohen and Torriello, 1996;Quarrell et al, 1998], and to suggest that it be diagnosed based on the narrow phenotype of the original reports by Baller [1950] and Gerold [1959]. Quarrell et al [1998] consider the cases presented by Ramos Fuentes et al [1994] and Galea and Tolmie [1990] to fit this narrower definition, and they recommend extensive cytogenetic and hematological studies for newly identified cases. The patient reported by Arena and Carlin [1989] may also fit these criteria, as he does not have additional malformations.…”
Section: Discussionmentioning
confidence: 99%
“…The wide phenotypic variability of what is considered Baller-Gerold syndrome in combination with the numerous reports of overlap with other disorders and revised diagnoses has led several investigators to question whether Baller-Gerold syndrome is a distinct entity [Cohen and Torriello, 1996;Quarrell et al, 1998], and to suggest that it be diagnosed based on the narrow phenotype of the original reports by Baller [1950] and Gerold [1959]. Quarrell et al [1998] consider the cases presented by Ramos Fuentes et al [1994] and Galea and Tolmie [1990] to fit this narrower definition, and they recommend extensive cytogenetic and hematological studies for newly identified cases. The patient reported by Arena and Carlin [1989] may also fit these criteria, as he does not have additional malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of malformations show a relatively high degree of variability. Any of the cranial sutures may be affected, but coronal involvement alone or combined is most common [Ramos Fuentes et al, 1994]. The upper limb defects range from asymmetric thumb or radial hypoplasia to bilateral agenesis of radius, first metacarpal, and thumb.…”
Section: Discussionmentioning
confidence: 99%